Pengaruh Earning per Share (EPS), Economic Value Added (EVA), Market Value Added (MVA) terhadap Return Saham pada Perusahaan Food And Beverage yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2020 - Rafael Erasdio; Risal Rinofah; Ratih Kusumawardhani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this study is to find out the effect of EPS, EVA, MVA on the return of shares for the period 2016-2020, invest in food and beverage companies listed on the Indonesia Stock Exchange. The variables used in the study were EPS, EVA, and MVA as independent variables, while stock returns as dependent variables. This is a quantitative study with a correlational approach. In the period 2016-2020, the subject of this study is a food and beverage company listed on the Indonesia Stock Exchange. Secondary data was obtained from 13 companies using the purposive sampling method. Then the data is processed and analyzed using multiple linear regression analysis. The results of the study using the t-test showed that the variable EPS and EVA had a significant effect on the variable Return of shares and the variable MVA did not have a significant effect on the variable Return of shares. While jasil test F states EPS, EVA, and MVA simultaneously affect the return of shares. Keywords: Earning Per Share; Economic Value Added; Market Value Added; return of shares